Hydrogeochemical Study of Free Groundwater in the Coastal Plain of Lattakia'S Basin (Latakia University Journal -Basic Sciences Series, 2019)
This study deals with the chemical properties of groundwater in the Coastal plain area of ​​ Lattakiabasin. The hydrogeological and hydrogeochemical studies showed a hydraulic connection between the aquifers of Quaternary, Neogene and Paleogene deposits. They form one watercourse with homogeneous properties in most of its parts.Groundwater samples were collected from eight sites in the coastal plain of Lattakia basin during three periods from 2017 to 2018. The samples were treated chemically and statistically to assess the quality of water for evaluating its validity for drinking water and agriculture purposes including inorder )Ca+2، Mg+2، K+، Na+،Cl-، SO4-2، HCO3-، NO3-، NO2-، NH4+، TDS، pH( And the understanding of the prevailing hydrogeological state.The treatment of the results of the analyzes showed that the fresh groundwater of continental origin is formed in open basins and has an active water exchange. It reflects the structure of bicarbonate in the genus of Magnesia. It refers to a stage or a preliminary stage in the development of the geochemical pattern of water. The values ​​of concentrations of all elements were within the permissible limits، so that it shows the possibility of using it for different uses for different uses.